1975
DOI: 10.1111/j.1749-6632.1975.tb35091.x
|View full text |Cite
|
Sign up to set email alerts
|

THE ACQUISITION OF RICKETTSIA TSUTSUGAMUSHI BY CHIGGERS (TROMBICULID MITES) DURING THE FEEDING PROCESS*

Abstract: INTRODUCTIONA fundamental concept in the ecology of ectoparasite-borne disease is that of the reservoir, or the wellspring of the infection in nature during interepidemic periods. In the case of chigger-borne rickettsiosis (scrub typhus), it has often been argued that chiggers (larval trombiculid mites) are not only the vectors but also the true reservoirs of the infection and that the small mammals (theraphions) that serve as hosts of the chiggers are of no importance as a source of rickettsiae for the chigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…[1][2][3][4][5] The chigger infects a rodent or human host when feeding on tissue fluid. [6][7][8] With no vaccine, scrub typhus prevention is a major challenge and infections may be fatal if untreated. 9 Orientia tsutsugamushi-infected mites are widely distributed throughout many Asian countries, northern Australia, and the western Pacific islands thereby placing an estimated one billion people at risk for scrub typhus, which averages one million cases annually.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The chigger infects a rodent or human host when feeding on tissue fluid. [6][7][8] With no vaccine, scrub typhus prevention is a major challenge and infections may be fatal if untreated. 9 Orientia tsutsugamushi-infected mites are widely distributed throughout many Asian countries, northern Australia, and the western Pacific islands thereby placing an estimated one billion people at risk for scrub typhus, which averages one million cases annually.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported by Rapmund's group that Rt is maintained by transovarial transmission in Rtcarrying colonies of L. fletcheri and L. arenicola that are known to be Rt-vector mites in Malaysia, and that most of the Rt-carrying mites were female (1,(11)(12)(13)(14)19). These and other authors have also reported that when non-Rt-carrying larvae were fed on infected laboratory mice, only a few of them acquired Rt through feeding, and no vertical transmission to the next generation through the egg was observed (10,18), though the number of mites examined was small. It is not yet clear whether oi-not Rt is maintained in L. pallidum by vertical transmission.…”
Section: Discussionmentioning
confidence: 78%
“…Although studies by Traub and others, 12 Walker and others, 8 Takahashi and others, 11 and Frances and others 10 have demonstrated that chiggers can acquire O. tsutsugamushi during the feeding process, to date mammals have not been shown to play a conclusive role in the cyclical transmission of this pathogen. 13 In spite of this, rodents play a key role in the epidemiology of scrub typhus, as rodents serve as maintenance hosts for the vector mites.…”
Section: Discussionmentioning
confidence: 99%
“…Frances and others 10 demonstrated that O. tsutsugamushi could be transmitted to co-feeding mites, and Takahashi and others 11 were able to infect chiggers fed on wild rodents; however, neither study determined if infected mites transmitted the rickettsiae to their eggs. Traub and others 12 were the first to document horizontal transmission of O. tsustsugamushi, although even this report discussed the possibility that the observation was not representative of natural transmission. In Thailand, Leptotrombidium deliense is the primary vector of scrub typhus; 13 however, several other species have been implicated as vectors and include L. chiangraiensis, 7 L. imphalum, 7 and Blankaartia acuscutellaris.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation